A new water mite species from a karstic cavern in southwestern Anatolia: Acherontacarus burduricus n. sp. (Acari, Hydrachnidia) - Gülle, Pinar; Boyaci, Yunus Ömer; Gülle İskender (Zootaxa, 2018)
A new species of Acherontacarus (Acari, Hydrachnidia), Acherontacarus burduricus n. sp., is described from interstitial waters of a small karstic cavern, in Burdur province (southwestern Anatolia). This is the third record of the genus from Turkey.